The Influence of Donor and Recipient Complement C3 Polymorphisms on Liver Transplant Outcome - Maria Pires; James Underhill; Abdel Douiri; Alberto Quaglia; Wayel Jassem; William Bernal; Nigel Heaton; Phillip Morgan; Richard Thompson; J. Michael Tredger (International Journal of Hepatology)
Despite early reports of an impact of complement C3 polymorphism on liver transplant patient and graft survival, subsequent evidence has been conflicting. Our aim was to clarify the contributions of donor and recipient C3 genotype, separately and together, on patient and graft outcomes and acute rejection incidence in liver transplant recipients. Eight donor/recipient groups were analyzed according to their genotype and presence or absence of C3 F allele (FFFS, FFSS, FSFF, FSFS, FSSS, SSFF, SSFS, and SSSS) and correlated with clinical outcomes of patient survival, graft survival, and rejection. The further impact of brain death vs. circulatory death during liver donation was also considered. Over a median 5.3 y follow-up of 506 patients with clinical information and matching donor and recipient tissue, five-year patient and graft survival (95% confidence interval) were 90(81-91)% and 77(73-85)%, respectively, and 72(69-94)% were rejection-free. Early disadvantages to patient survival were associated with donor C3 F variant, especially in brain-death donors. Recipient C3 genotype was an independent determinant of graft survival by Cox proportional hazards analysis (hazard ratio 0.26, P=0.04), and the C3 F donor variant was again associated with worse liver graft survival, particularly in brain-death donors. C3 genotype did not independently determine rejection incidence, but a greater proportion of recipient C3 F carriers were rejection-free in the circulatory death, but not the brain-death cohort. Cox proportional hazards analysis revealed significant effects of acute rejection on patient survival (hazard ratio 0.24, P=0.018), of retransplantation on rejection risk (hazard ratio 6.3, P=0.009), and of donor type (circulatory-death vs. brain-death) on rejection incidence (hazard ratio 4.9, P=0.005). We conclude that both donor and recipient complement C3 genotype may influence patient and graft outcomes after liver transplantation but that the type of liver donor is additionally influential, possibly via the inflammatory environment of the transplant.